Sec61p mediates export of a misfolded secretory protein from the endoplasmic reticulum to the cytosol for degradation. - Pilon, M (1997)
Degradation of misfolded secretory proteins has long been assumed to occur in the lumen of the endoplasmic reticulum (ER). Recent evidence, however, suggests that such proteins are instead degraded by proteasomes in the cytosol, although it remains unclear how the proteins are transported out of the ER. Here we provide the first genetic evidence that Sec61p, the pore-forming subunit of the protein translocation channel in the ER membrane, is directly involved in the export of misfolded secretory proteins. We describe two novel mutants in yeast Sec61p that are cold-sensitive for import into the ER in both intact yeast cells and a cell-free system. Microsomes derived from these mutants are defective in exporting misfolded secretory proteins. These proteins become trapped in the ER and are associated with Sec61p. We conclude that misfolded secretory proteins are exported for degradation from the ER to the cytosol via channels formed by Sec61p.